LAPAROSCOPIC CHOLECYSTECTOMY IN PATIENTS WITH CHRONIC CALCULOUS CHOLECYSTITIS WHICH IS COMPLICATED BY GALLSTONE–INTESTINAL BILE FISTULA - Khvorostov, E.D.; Zakharchenko, Yu.B.; Shapovalov, A.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The analysis of 4 patients with chronic calculous cholecystitis in combination with gallstone-intestinal bile fistula treatment was carried out. 3 patients had gallstone-duodenal bile fistula, 1 patient had gallstone-transverse-colon bile fistula. The diagnostics of gallstone-intestinal bile fistula in patients with chronic calculous cholecystitis is difficult and required wide investigation using expensive invasive methods. Fistula was diagnostic in the time laparoscopic cholecystectomy. The current of operative intervention was changed. Technical methods were used for the fistula removal. Gallstone-intestinal bile fistula may be removed in the time laparoscopic cholecystectomy using minilaparotomy in right subcostal area for extraction of gallbladder and suture intestinal wall without considerable trauma increase due to operation.